Implementasi Reformasi Birokrasi Bidang Perizinan Pananaman Modal di Kabupaten Kuningan - Haris Budiman; Suwari Akhmaddhian (UNIFIKASI : Jurnal Ilmu Hukum, 2014)
Bureaucratic reform is essentially an attempt to reform and fundamental changes to the systems of governance in order to reach the goal of bureaucratic reform to accelerate achievement of good governance and efforts to improve support for local government in Increasing performance. Bureaucracy reform program running which consisted principally of institutional reform, human resources management reform and information technology support in the licensing process. Institutional reform is to establish a new agency that handles the licensing process in the past, integrated licensing process to go through the different agencies and with the reform of the bureaucracy in the licensing process united in one body that is unified, improve human resources through training and increase the transparency of information through the management information technology support. Bureaucratic reform in investment licensing and the area is already under way in an effort to improve service to the community that good governance is not just adream and soon became a reality.Keywords: Licensing, Service, Bureaucratic Reform.